The Role Of Social Media In Building Consumer Trust In Product - Kartomo, Thomas (Kompartemen: Kumpulan Orientasi Pasar Konsumen, 2024)
This study explores the role of social media in building consumer trust in products in the digital era. Using a qualitative method, the research examines consumers' perspectives and experiences with social media as a transparent and interactive marketing platform. Based on in-depth interviews and content analysis, the study finds that consumer reviews on social media significantly influence purchasing decisions, especially those reviews that include visuals and testimonials from other users. Additionally, brand transparency and responsiveness to consumer feedback highlight the importance of openness in fostering trust. Educational content provided by brands also enhances consumers' positive perceptions, as it offers additional value beyond typical promotions. Direct interaction between consumers and brands on social media strengthens the emotional connection, creating a sense of appreciation and trust toward the brand. The findings provide practical insights for companies to strategically leverage social media in establishing sustainable relationships with consumers. By focusing on aspects of consumer review credibility, transparency, educational content, and responsive interaction, companies can increase consumer trust in their products.